Science Learning Based on Deep Learning Approach Assisted by Educational Games to Improve Student Learning Outcomes at Parthome Santiwit Songkhla Technological College Thailand - Rini Rahmita Aritonang; Iskandar Safri Hasibuan; Jalilah Azizah Lubis; Nurlaila Hazeemalee (Jurnal Penelitian Pendidikan IPA, 2026)
The purpose of this study was to enhance fourth-grade science students' learning outcomes at Santiwit Elementary School, Songkhla Technological College, Thailand, by utilizing deep learning techniques in conjunction with educational games. While educational games were utilized as engaging and pertinent learning resources, the deep learning approach was utilized to promote deeper conceptual knowledge, active participation, and critical thinking abilities. The classroom action approach used in this study was carried out in phases, including preparation, execution, observation, and reflection. According to the study's findings, student learning outcomes—both in terms of cognitive abilities and involvement in the learning process—have significantly improved. Pupils grew more engaged, animated, and capable of relating scientific ideas to pertinent educational opportunities. It has also been demonstrated that using educational games can boost learning motivation and foster a joyful learning environment. Based on these results, it can be said that fourth-grade students' science learning achievement is enhanced by the deep learning approach aided by educational games.